2019
DOI: 10.1021/acs.jcim.9b00626
|View full text |Cite
|
Sign up to set email alerts
|

Deep Transferable Compound Representation across Domains and Tasks for Low Data Drug Discovery

Abstract: The main problem of small molecule-based drug discovery is to find a candidate molecule with increased pharmacological activity, proper ADME, and low toxicity. Recently, machine learning has driven a significant contribution to drug discovery. However, many machine learning methods, such as deep learning-based approaches, require a large amount of training data to form accurate predictions for unseen data. In lead optimization step, the amount of available biological data on small molecule compounds is low, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
(65 reference statements)
1
27
0
Order By: Relevance
“…Unlike other ADMET properties, toxicity data is relatively well-known to the public because of the Tox21 challenge in 2014. Therefore, methodology-based studies have recently emerged, and benchmarked against major toxicity datasets including the Tox21 dataset [76,[184][185][186][187]. All of the studies proposed deep learning-based novel architectures to predict the compound toxic-related properties.…”
Section: Toxicitymentioning
confidence: 99%
“…Unlike other ADMET properties, toxicity data is relatively well-known to the public because of the Tox21 challenge in 2014. Therefore, methodology-based studies have recently emerged, and benchmarked against major toxicity datasets including the Tox21 dataset [76,[184][185][186][187]. All of the studies proposed deep learning-based novel architectures to predict the compound toxic-related properties.…”
Section: Toxicitymentioning
confidence: 99%
“…Overall, three types of machine learning methods, including supervised, semi-supervised, and unsupervised techniques have been used in the scope of drug discovery [15]. Also, it has been shown that some modified and improved versions of the present approaches such as deep neural networks can yield better predictive models [16]. Overfitting and insufficient amounts of data are the main challenges in generating an appropriate predictive model [17,18].…”
Section: -Backgroundmentioning
confidence: 99%
“…Overall, three types of machine learning methods such as supervised, semi-supervised, and unsupervised techniques have been used in drug discovery scope (15). Also, it has been shown that some modified and improved versions of the approaches such as deep neural networks can lead to better predictive models (16). Overfitting and lack of enough number of data are the main challenges in generating an appropriate predictive model (17,18).…”
Section: -Related Workmentioning
confidence: 99%